Crack path and liquid metal embrittlement specificity of austenitic steels in mercury at room temperature. (1st July 2022) - Auger, Thierry; Barkia, Bassem; Héripré, Eva; Michel, Vincent; Mutel, Denis; Guillot, Ivan; Hamouche, Zehoua; Medina-Almazàn, Liliana
Abstract: A liquid metal embrittlement specificity of three austenitic steels with increasing nickel content (304 L, 316 L and 316L(N)) is studied in liquid mercury in the axisymmetric notched geometry. Only the low nickel alloys are susceptible to LME. The crack path of an austenitic steel fracture induced by liquid mercury has been elucidated at microstructural scale. Deformation induced martensite (γ(fcc) → α'(bcc)) of the low nickel steels induces numerous α'/α' interfaces at small scale that are susceptible to be embrittled. Because the only steel that resists LME is the one that shows stability over α' phase change due mostly to its higher nickel content, a point confirmed by X Ray fractography, it is inferred that the major factor contributing to the LME sensitivity at room temperature is the α' phase formation in unstable austenitic steels during plastic strain. This provides a sound rationale on how to prevent mercury induced embrittlement with austenitic steels. Graphical abstract: Image, graphical abstract